Scale-Dependent Habitat Use from an Individual-Based Perspective: The Case of the Endangered Darwin’S Fox Living in Heterogeneous Forest Landscapes - Vergara-Egert, P; Moreira-Arce, D; Alaniz-Baeza, A (Springer Science and Business Media B.V., 2021)
Context: Understanding how rare and threatened species respond to habitat heterogeneity at different spatial scales requires unbiased population-level parameters incorporating individual variability in occurrence and detection probabilities. Objectives: We used a Bayesian approach integrating capture-recapture data into an occupancy framework. We assessed the response of Darwin’s fox—a forest-specialist mesocarnivore—to habitat heterogeneity in landscapes with low and moderate fragmentation levels in Chiloé Island, Southern Chile. Our model accounted for differences in capture, occupancy and detection probability among individuals. Results: We captured 33 Darwin’s foxes, totaling 65 captures/recaptures in 62 different traps (720 trap/nights). Foxes’ detection increased across years and females (n = 15; mean detection probability ± SE 0.07 ± 0.03) were less detected than males (n = 18; 0.11 ± 0.04). Mean [95% BCI] of Darwin’s fox occupancy (ψ) varied from 0.59 [0.43–0.75] in the landscape with the largest mean of forest patch size, to 0.24 [0.22–0.28] in the less heterogeneous landscape. Species occupancy decreased with distance from freshwater bodies. We also found a significant interaction between distance from freshwater bodies and total edges at landscape level, resulting in high occupancy values (> 0.5) in landscapes dominated by forest ecotones. Conclusions: Our findings suggest the effect of habitat heterogeneity on local populations of the threaten Darwin’s fox in Chiloé Island is modulated by the individual response to habitat attributes at local and landscape scales, but also by emergent cross-scale interactions. © 2021, Springer Nature B.V.